السرد الصحراوي في رواية الكناش لسليم عبادو - قدوري, نعيمة; فار, سارة; مسعودي, عائشة (University of Eloued جامعة الوادي, 2024)
تقدم هذه المذكرة دراسة في إحدى الروايات الجزائرية المعاصرة، وهي رواية الكنّـاس " للكاتب الجزائري "سليم عبادو والتي اتخذت الصحراء مسرحا لأحداثها فجمعت بين الحقائق العلمية والتخييل الروائي في تركيبة سردية فريدة من نوعها يفرض فيها الفضاء الصحراوي نفسه بل ويسيطر على مسار الرواية بأكمله. حيث تبلورت هذه الدراسة في مدخل وفصلين حيث عرض المدخل مفاهيم متخيل الصحراء في السرد الروائي والصحراء موضوعا للسرد، اما الفصل الاول فكان محوره مكونات السرد الصحراوي في الرواية الجزائرية، اما الفصل الثاني فبحثنا فيه على أهم ما انطوت عليه رواية الكناس من أبعاد شخصية، ووصف صحراء الوادي، والتراث الشعبي الصحراوي، وغرائبية الصحراء، وجدليه البطل الصحراوي والفضاء الاخر. This diary offers a study of a contemporary Algerian novel. The novel of Al Kannas " The Sweeper " by Salim Habado, which took the desert as its theater of events, combining scientific facts and fictional imagination in a unique narrative structure in which the desert space imposes itself and even dominates the entire course of the novel. The introduction introduces the concepts of the desert imaginary in the novel and the desert as a subject of the narrative. As for the first chapter, it focused on the components of the Saharawi narrative in the Algerian novel. As for the second chapter, we examined the most important aspects of the novel, including personal dimensions, the description of the Wadi desert, Saharawi folklore, the mythology of the desert, and the dialectic of the Saharawi hero and the other space.
أدب حديث ومعاصر
Keywords: : المتخيل، الفضاء، الصحراء، السرد الصحراوي; Imagined; outer space; the desert; The desert narration